Disaster Management Concept of Muhammadiyah Disaster Management Centre in Ponorogo, Indonesia - Yusuf Adam Hilman (Otoritas : Jurnal Ilmu Pemerintahan, 2018)
Muhammadiyah Disaster Management Centre as an organization under Muhammadiyah Union, has a unique disaster management model, although it has not been established yet, MDMC has proven its existence. This progress is very interesting because it is very closely related to the Islamic concept which makes this organization different from other organizations. This background is very interesting to study. Besides, the concept and pattern of MDMC organization has not been popularly identified yet. This study aims to know and describe management disaster concept proposed by Muhammadiyah Disaster Management Centre (MDMC). It is to verify organizational pattern and Muhammadiyah Disaster Management Centre (MDMC) profile. This study utilizes interpretative paradigm with qualitative model. Based on the study conducted, it can be summarized that Al-Maun spirit has influenced and characterized MDMC organization on implementing disaster management activities. The spirit is reflected by how the management of mutually supportive organizations to achieve common goals. It is in order to help each other or (mustadi'in). This is achieved by having  partnership with Muhammadiyah autonomous institutions, as well as other parties such as government and private parties. There is a humanist concept beyond Al-Maun spirit. It is sharing and caring for people. It is implemented by MDMC through disaster management activities, from identifying, reconstructing, rehabilitating, to normalizing the victims.  Seen from its existence, these activities lead MDMC to have a good vision in implementing disaster management.